2019
DOI: 10.1080/0886022x.2019.1620774
|View full text |Cite
|
Sign up to set email alerts
|

Pathological spectrum of glomerular disease in patients with renal insufficiency: a single-center study in Northeastern China

Abstract: Background: To investigate the pathological spectrum of glomerular disease in patients with renal insufficiency (RI) from 2008 to 2017. Methods and results: We calculated the estimated glomerular filtration rate (eGFR) with the Chronic Kidney Disease Epidemiology Collaboration creatinine (CKD-EPI) equation and defined RI as an eGFR <60 ml/min/1.73 m 2 . A total of 969 RI patients were included in our study. IgA nephropathy (IgAN) was the most common subtype of primary glomerulonephritis (37.2%). The frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
(34 reference statements)
8
11
1
Order By: Relevance
“…The percentage of elderly patients undergoing renal biopsy in our center is similar to that in previous reports [11]. As previously reported in multiple studies [12][13][14][15][16], the percentage of elderly patients undergoing renal biopsy, over the years, has increased in our center. Among elderly and non-elderly patients with renal disease, the risk of undergoing renal biopsy is comparable [6,17].…”
Section: Discussionsupporting
confidence: 89%
“…The percentage of elderly patients undergoing renal biopsy in our center is similar to that in previous reports [11]. As previously reported in multiple studies [12][13][14][15][16], the percentage of elderly patients undergoing renal biopsy, over the years, has increased in our center. Among elderly and non-elderly patients with renal disease, the risk of undergoing renal biopsy is comparable [6,17].…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies from China showed that membranous nephropathy is increasing [6,11], and this result might be associated with air pollution by particulate matter 2.5 (PM 2.5 ) [12]. However, the current study [9] did not show any significant change in frequency of membranous nephropathy according to time course.…”
contrasting
confidence: 81%
“…Our study also showed a similar pattern of renal injury in the form of rising creatinine or proteinuria, among many patients diagnosed with renal failure secondary to hypertension (58%). Renal vasculitis is more common in the elderly than in the young [ 1 , 6 ]. Only 2.2% of our cases showed crescentic glomerulonephritis.…”
Section: Discussionmentioning
confidence: 99%
“…CKD is a common public health-related issue with a higher incidence rate and poorer prognosis in recent years. It is a financially challenging disease globally and is frequently seen in older adults [ 1 ]. As the life span of individuals increases, the patients with acute and chronic kidney disease continue to survive longer [ 2 ].…”
Section: Introductionmentioning
confidence: 99%